Correction: Wang et al. Anti-Metabolic Syndrome Effects of Fucoidan from Fucus vesiculosus via Reactive Oxygen Species-Mediated Regulation of JNK, Akt, and AMPK Signaling. Molecules 2019, 24, 3319 - Xueliang Wang; Xindi Shan; Yunlou Dun; Chao Cai; Jiejie Hao; Guoyun Li; Kaiyun Cui; Guangli Yu (Molecules, 2025)
In the original publication [...]